2022
DOI: 10.1088/2752-5724/ac7068
|View full text |Cite
|
Sign up to set email alerts
|

Efficient nanozyme engineering for antibacterial therapy

Abstract: Antimicrobial resistance (AMR) has posed a huge threat to human health. It is urgent to explore efficient ways to suppress the spread of AMR. Antibacterial nanozymes has become one of the powerful weapons to combat AMR due to their enzyme-like catalytic activity with a broad-spectrum antibacterial performance. However, the inherent low catalytic activity of nanozymes limits their expansion into antibacterial applications. In this regard, a variety of advanced chemical design strategies have been developed to i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 132 publications
0
21
0
Order By: Relevance
“…[17][18][19] As such, most present studies on the action mechanism of amphipathic cationic peptides (e.g., LL-37) are performed using micromolar agents based on a combination of many biochemical techniques such as the fluorescence localization imaging and downstream cytokine detection. 5,[20][21][22][23] The effect of nanomolar peptides, which might also exist in the physiological circumstances, is significantly neglected. On the one hand, LL-37 is produced by specific cells at all times and the physiological concentration of it covers a wide range (from nM to μM).…”
Section: Introductionmentioning
confidence: 99%
“…[17][18][19] As such, most present studies on the action mechanism of amphipathic cationic peptides (e.g., LL-37) are performed using micromolar agents based on a combination of many biochemical techniques such as the fluorescence localization imaging and downstream cytokine detection. 5,[20][21][22][23] The effect of nanomolar peptides, which might also exist in the physiological circumstances, is significantly neglected. On the one hand, LL-37 is produced by specific cells at all times and the physiological concentration of it covers a wide range (from nM to μM).…”
Section: Introductionmentioning
confidence: 99%
“…25−27 Researchers have attempted to regulate the balance of the amphiphilic structure of antimicrobial polymers to achieve optimal selectivity toward bacteria. 28,29 of the amphipathic structure of nylon-3 copolymers and reported that high selectivity could be achieved when the cationic segments (i.e., blocks of amphipathic copolymers) were ∼50% of the polymer. 30 Similarly, Kuroda and Palermo reported that when regulating the proportion of cationic segments from 30 to 100%, polymethacrylate copolymers exhibited top selectivity at a 50% ratio of cationic segments.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Both the inner and outer membranes of Gram-negative bacteria and cytoplasmic membrane of Gram-positive bacteria contain at least 15% of anionic lipids (such as phosphatidylglycerol [PG] and cardiolipin), whereas the mammalian plasma membrane mainly contains zwitterionic lipids (including phosphatidylcholine and sphingomyelin) and a small amount of negatively charged lipids (phosphatidylserine and phosphatidylinositol), which are primarily distributed in the inner leaflet of the plasma membrane. Additionally, bacterial cells have additional cell envelope components, the peptidoglycan cell wall, providing sufficient mechanical strength to endure changes in osmotic pressure, and other components such as negatively charged lipopolysaccharide in the outer leaflet of the outer membrane of Gram-negative bacteria and teichoic acids in the cytoplasmic membrane of Gram-positive bacteria further increase the negative charge of bacterial cells, and the influence of exogenous pH changes on the bacterial membrane has not been reported. Given the differences in charge and composition between bacterial and mammalian cell membranes, studies have reported that the amphiphilic balance between the cationic and hydrophobic segments greatly influences the antimicrobial and hemolytic activities of antimicrobial polymers. Researchers have attempted to regulate the balance of the amphiphilic structure of antimicrobial polymers to achieve optimal selectivity toward bacteria. , For example, Gellman et al regulated the balance of the amphipathic structure of nylon-3 copolymers and reported that high selectivity could be achieved when the cationic segments (i.e., blocks of amphipathic copolymers) were ∼50% of the polymer . Similarly, Kuroda and Palermo reported that when regulating the proportion of cationic segments from 30 to 100%, polymethacrylate copolymers exhibited top selectivity at a 50% ratio of cationic segments …”
Section: Introductionmentioning
confidence: 99%
“…Membrane curvature is crucial for various cellular functions, including the regulation of lipid and protein distribution, the formation of functional domains, and the control of cell interactions with substances. , ,, However, despite proteins such as N-BAR being able to modulate membrane shape or curvature, the mechanism underlying curvature generation remains poorly understood. In this study, we investigate this mechanism by utilizing simulations and a theoretical model to evaluate the impact of MAPs on membrane curvature alteration, which also facilitates comprehension of the biological functions of related proteins.…”
mentioning
confidence: 99%
“…The current models on MAP–membrane interactions primarily focus on the membrane poration and/or permeabilization of MAPs, with limited understanding of their potential membrane-specific actions. In related studies investigating the mechanism of MAP–membrane interaction, oversimplified model cell membranes containing only phosphatidylcholine (PC) and/or phosphatidylglycerol (PG) have been utilized. , However, in reality, cell membranes exhibit a much more intricate lipid composition that varies depending on the type of cell . Additionally, lipids actively regulate protein functions through specific interactions with proteins. Moreover, efforts to improve clinical applications of membrane-active peptides (MAPs) as transporters or bactericidal agents may paradoxically result in stronger permeabilization ability but also severe side effects such as membrane lysis and cytotoxicity. Unfortunately, the conflicting effects of MAPs have yet to be resolved and have been largely overlooked to date. Furthermore, recent experiments have revealed unexpected membrane activities of MAPs.…”
mentioning
confidence: 99%